Pengaruh penggunaan metode teka-teki silang terhadap pengajaran kosakata pada siswa Di SMA Swasta Mohammadiyahu - Dewi Yunita Putri; Devy Aisyah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
The purpose of this research is to find out the influence of using the crossword puzzle media on Vocabulary learning of students at the junior high school Muhammadiyah Sulit Air in the seventh grade and to find out the statistically significant difference between the experimental group using the crossword puzzle media and the control group did not use the crossword puzzle media. The research methodology is quantitative research in the experimental way. The researcher used the research design is Quasi Experimental Design, with the type of Nonequivalent Control Group Design. The researcher used three data collection tools: interview guide, observation guide, and exam. After researchers use Crossword Puzzle media in vocabulary learning, there is an influence on vocabulary teaching with a maximum result of 100 and a minimum result of 45. Then, Researchers found that the to result was greater than the tt result, which was 3.69 > 2,539. Therefore, the alternative hypothesis (Ha) is accepted and the nihilistic hypothesis (Ho) is rejected. The point is that there is a difference between the results of vocabulary learning using crossword puzzle media and without using crossword puzzle media. The conclusion of this research is that there is an influence of the use of Crossword Puzzle media of students at the Junior Islamic High School Muhammadiyah Sulit Air.